Hallux valgus assessment on X-ray and Magnetic resonance Imaging (MRI): Correlation with qualitative soft tissue and internal derangement findings on MRI. Issue 113 (April 2019) - Hummel, Jed; Skweres, Justin; Heineman, Nathan; Dessouky, Riham; Xi, Yin; Zhang, Lihua; Wukich, Dane K.; Chhabra, Avneesh
Abstract: Aim: Radiographs (X-rays) are used for the preoperative assessment of hallux valgus (HV). Our purpose was to determine how well quantitative measurements of HV on radiographs and MRI correlate with the qualitative soft tissue and internal derangement findings on MRI. Materials and methods: After IRB approval, 56 consecutive patients with MRI and radiographs of the foot were retrospectively reviewed. Two trained readers independently evaluated radiographs, measuring hallux valgus angle (HVA) and intermetatarsal angle (IMA). Two separate readers assessed qualitative MRI data by evaluating 21 different soft tissue and bony features. Statistical analysis included inter-reader reliability (IRR) and correlation of quantitative and qualitative findings. Results: Excellent IRR (ICC = 0.89–0.96) was observed for radiograph and MRI measurements of the hallux valgus severity. For qualitative assessments on MRI, IRR was good to excellent for all features (ICC = 0.63–0.9). No significant difference was found for HVA or IMA between normal and abnormal qualitative MRI features. No statistically significant correlation between the severity of hallux valgus and injury to hallux joints and supporting structures was found. Conclusion: Hallux valgus measurements are reliable on x-rays and MRI and qualitative findings of 1st MTP joint show good to excellent inter-reader agreement on MRI. No statistically significant correlations exist between the severity of hallux valgus and qualitative MRI findings.